DOA DALAM GENGGAMAN: ANALISIS PENGGUNAAN APLIKASI WIRID REMINDER DI KALANGAN MILENIAL URBAN - Siti Maqfirah (NIHAYAH: Journal of Islamic Studies, 2025)
The rise of digital technology has reshaped how urban millennials practice their faith, particularly in daily devotions such as wirid and prayer. This article explores the phenomenon of wirid reminder app usage among Indonesian urban millennials, focusing on usage patterns, motivations, and spiritual-psychological impacts. Employing a mixed-methods approach, data were gathered through an online survey of 200 active users, in-depth interviews with 15 intensive users and 5 app developers, as well as digital observation of five popular applications and related online user forums. Findings reveal that 75% of users access the app during commutes or work breaks, with notification and progress tracking features being the most popular. Key motivations include the need for spiritual consistency and peer influence. While the app supports the reinforcement of spiritual routines, some users experience notification fatigue due to excessive alerts. Additionally, ethical concerns arise regarding the monetization model of premium subscription for advanced features, highlighting a tension between digital convenience and commodification of religious practice. The article recommends that app developers incorporate culturally contextualized content and promote mindful spiritual engagement rather than fostering dependency on digital reminders. This study underscores the need for a holistic and ethical framework in designing digital spirituality platforms for contemporary users.